1995
DOI: 10.1080/02652039509374347
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ochratoxin A in beer

Abstract: Because of concern about possible transmission of ochratoxin A (OA) from contaminated grain adjuncts, development of a sensitive method for its determination in beer was investigated. Solid phase extraction (SPE) on C-18 and silica gel columns in series and on an immunoaffinity column (OchraTest) were used to obtain extracts for quantitation by reverse phase liquid chromatography with fluorescence detection. The standard curve was linear in the range 2.5-50 pg OA injected and detection limits for both methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
2
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 10 publications
2
45
2
7
Order By: Relevance
“…The incidence found in Brazilian beer in the present survey (4.8%) is therefore low. The levels found, on the other hand are higher then the levels reported by other countries by various orders of magnitude 12,13,21,26,27,35,47,52,53 .…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…The incidence found in Brazilian beer in the present survey (4.8%) is therefore low. The levels found, on the other hand are higher then the levels reported by other countries by various orders of magnitude 12,13,21,26,27,35,47,52,53 .…”
Section: Resultscontrasting
confidence: 57%
“…German beers (35 samples) were analyzed by DEGELMANN et al 13 and OTA levels in the range of 0.1-0.2 ng.mL -1 were found in 9 beer samples, 21 samples contained trace amounts of OTA (<0.1 ng.mL -1 ) and in 5 samples no OTA was detectable. SCOTT and KANHERE 35 found traces of OTA in 26 out of 46 samples of Canadian and imported beers. In Denmark, JORGENSEN 21 found OTA in 21 samples of beer analyzed in concentrations ranging from 0.0001 to 0.160 ng.mL -1 , with a mean of 0.049 ng.mL -1 .…”
Section: Introductionmentioning
confidence: 98%
“…In Canada, Scott and Kanhere found OTA in 26 of 41 tested beer samples with the OTA value to 200 ng·l -1 (Scott and Kanhere, 1995). In 2005, 88 beers from the retail shop in Spain were analyzed.…”
Section: Výskyt Mykotoxinů V Pivech Z Obchodní Sítěmentioning
confidence: 99%
“…Bennett et al used zearalenonecontaminated maize for ethanol production, but the toxin was not degraded and remained in the fermentation residues [140]. Mycotoxins can often be found in beer and wine, but they are partly degraded and partly transferred to beer, with part remaining in the draff during the fermentation process [141][142][143][144]. Studies on alcohol fermentation by S. cerevisiae using grains (barley, corn or wheat) contaminated with DON [122,123,145,146] showed that DON was stable to the alcoholic fermentation process and not metabolised by Saccharomyces yeasts.The mycotoxin concentration remaining in the draff (DDGS) may be relatively high and so traditional alcohol fermentation is not a very effective means of detoxifiying feed material.…”
Section: Impact Of Enzymes On Alcohol Fermentation Of Mycotoxin Contamentioning
confidence: 99%